DIGITAL COMPETENCE OF THE TEACHER OF THE NEW SCHOOL OF AUSTRIA - Solomakha, Angelika (Educological discourse, 2018)
Paying attention to the global changes that have taken place in the world in recent decades with rapid dichatolization of all spheres of human life in general, and education of all levels, in particular, the international community and governments of all countries are developing new strategies for the educational process aimed at preparing people for life in the digital future. Therefore, the article examines the experience of reforming the education of the European Union countries, and explores the experience of reforming Austrian secondary and vocational education and the concept of the new digital school Schule 4.0. - jetzt wird’s digital ». The study shows that the compulsory component of the professional competence of modern Austrian teachers, including foreign language teachers, is digital competence. Austria’s Federal Ministry of Education, Science and Research (das Bundesministerium für Bildung, Wissenschaft, Forschung Österreichs) in cooperation with leading Austrian universities has developed a series of documents detailing the steps to implement Schule 4.0. - jetzt wird’s digital ». The article analyzes the strategic documents of pedagogical training at Austrian universities about the development of digital competence and found that a future teacher of a modern Austrian school, including a foreign language teacher, should develop the digital skills from the beginning of training at a pedagogical university and reach the level of "expert" in accordance with the Digital Competence Framework (2016 and 2017) while getting a master’s degree.